2021
DOI: 10.3390/ijms22041684
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Mesenchymal Transition and Senescence in the Retinal Pigment Epithelium of NFE2L2/PGC-1α Double Knock-Out Mice

Abstract: Age-related macular degeneration (AMD) is the most prevalent form of irreversible blindness worldwide in the elderly population. In our previous studies, we found that deficiencies in the nuclear factor, erythroid 2 like 2 (NFE2L2) and peroxisome proliferator-activated receptor gamma coactivator 1-α (PGC-1α) genes caused AMD-like pathological phenotypes in mice. In the present work, we show hijacked epithelial-mesenchymal transition (EMT) due to the common loss of PGC-1α and NFE2L2 (double knock-out, dKO) gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Autophagy can directly regulate EMT by selective degradation of EMT molecular triggers [128]. We partly confirmed Saint-Geniez's conclusions, showing that cells obtained from PGC-1α/NFE2L2 dKO aged mice underwent EMT [129]. In that study, we also observed an increased immunoreactivity of senescence markers p16, DEC1 (deleted in esophageal cancer 1), and HMGB1 (high mobility group box protein 1).…”
Section: Pgc-1α May Link Telomerase With Amdsupporting
confidence: 86%
“…Autophagy can directly regulate EMT by selective degradation of EMT molecular triggers [128]. We partly confirmed Saint-Geniez's conclusions, showing that cells obtained from PGC-1α/NFE2L2 dKO aged mice underwent EMT [129]. In that study, we also observed an increased immunoreactivity of senescence markers p16, DEC1 (deleted in esophageal cancer 1), and HMGB1 (high mobility group box protein 1).…”
Section: Pgc-1α May Link Telomerase With Amdsupporting
confidence: 86%
“…The possibility of EMT occurring in the RPE during the advanced stages of AMD is well established, and it has also been observed in AMD-simulating cell and animal models (Ishikawa et al 2016;Chen et al 2020;Shu et al 2020;Zhou et al 2020;Wang et al 2021). In a recent article of ours, we showed an AMDresembling mouse model exhibiting typical EMT-style morphological changes in the RPE, as well as alterations in the cellular levels of EMTrelated transcription factors and cellular-level markers such as Snail, vimentin and OB-cadherin (Blasiak et al 2021). Studies specifically focusing on EMT-related markers in the systemic circulation of AMD patients have not been published previously.…”
Section: Introductionmentioning
confidence: 51%
“…Multiple pathways (e.g., TGF-β, Wnt, miRNA, oxidative stress/Nrf2, etc.) are known to play a role in EMT by RPE and this topic has been reviewed extensively recently by others (Yang et al, 2015;Shu et al, 2020;Zhou et al, 2020;Blasiak et al, 2021). However, the molecular cues that guide RPE cells transdifferentiating into macrophage-or fibroblast-like phenotypes remain to be fully elucidated.…”
Section: Wound Healing In the Subretinal Spacementioning
confidence: 99%